(Historians of the Crusades and their Sources (1096-1291 AD - Shukairat, Hussein Raja (Journal of Humanities & Social Sciences, 2019)
Following this research attempts mo’rkhwa crusades in codifying what be contemporary with him or saw him or took him, relying on splitting these historians to Western historians or European sources which include Greek and Latin. Eastern sources, which include Arabic, Syriac, Armenian or something known as Saladin historians. There is no doubt that article and a wide and long study period. But until search is to focus on the sources of the Crusades and the attempt to give a picture if the author and the source and provide a simple overview of each source are outlined these sources at the end of the study covered all list.